Formulasi Dan Evaluasi Sediaan Sabun Cair Scrub Dari Sari Buah Melon (Cucumis melo L.) - Ervina Syahfitri Lubis; Indah Pertiwi; Meiva Amelia Lubis (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Melon fruit (Cucumis melo L.) contains bioactive compounds such as vitamin C, β-carotene, flavonoids, polyphenols, pectin, and superoxide dismutase (SOD) enzyme that theoretically have potential antioxidant and skin care benefits in topical preparations. This study aimed to formulate and evaluate the physical quality of liquid scrub soap from melon fruit juice at varying concentrations of 0% (F0/blank), 5% (F1), 10% (F2), and 15% (F3), using coffee grounds as a natural exfoliating agent. Physical quality evaluations included organoleptic testing, foam height and stability, pH, and viscosity according to SNI 06-4085-1996. Data were analyzed using One-Way ANOVA followed by Tukey HSD post-hoc test (α=0.05). Organoleptic results showed all formulas were white, liquid, melon-scented, and contained brown scrub granules. One-Way ANOVA showed that melon fruit juice concentration significantly affected all tested parameters (p<0.05). The average pH of F1, F2, and F3 were 8.53±0.06ᵇ, 9.17±0.12ᶜ, and 9.77±0.06ᵈ, meeting SNI requirements (pH 8–11). Average foam heights of F1, F2, and F3 were 105.00±1.00ᵇ mm, 125.67±1.53ᶜ mm, and 154.00±2.65ᵈ mm, with foam stability of 82.27±1.76ᵃᵇ%, 85.13±0.32ᵇᶜ%, and 87.03±1.47ᶜ%, all meeting SNI standards (13–220 mm) and stability threshold ≥70%. Viscosity of F1, F2, and F3 were 1,633±57.74ᵇ cP, 2,000±100.00ᶜ cP, and 2,567±57.74ᵈ cP, within the acceptable range (400–4,000 cP). Tukey HSD confirmed significant differences among all formulas for pH, foam height, and viscosity parameters. It was concluded that melon fruit juice can be successfully formulated into a liquid scrub soap and all formulas met the established physical quality requirements. Formula F3 at 15% concentration produced the best results. Further research is needed to evaluate the biological activity of the preparation, including antioxidant testing, exfoliation efficacy, and skin irritation studies.